CULINARY ECHOES OF LOMBOK: NARASI RASA DALAM JEJARING SOSIAL - I Wayan Astraguna; Komang Reza Kartika; I Made Ngurah Oka Mahardika (Institut Agama Hindu Negeri Gde Puda Mataram, 2025)
This study aims to explore in depth how the narrative and representation of Lombok’s traditional cuisine are constructed and disseminated through social media, while also evaluating the effectiveness of digital media as a promotional strategy for regional tourism development. The research is grounded in the fact that, despite Lombok’s abundant natural resources and strong tourism potential, the sector has yet to become a primary economic driver. Similarly, local culinary heritage—which holds substantial appeal for tourists—has not been strategically leveraged by formal institutions through digital platforms. Adopting a descriptive qualitative approach, data collection was carried out through digital observation, in-depth interviews, and documentation of social media content. Informants were selected using purposive sampling based on their active engagement in producing Lombok culinary content and their involvement in digital tourism promotion. Data analysis followed the Miles and Huberman interactive model, which includes data reduction, data display, and conclusion drawing. The findings indicate that Lombok culinary content circulating on social media predominantly features iconic dishes such as ayam taliwang, plecing kangkung, and sate rembiga. Most widely shared content is created by non-formal actors, including food vloggers and individual travelers, while contributions from formal stakeholders remain minimal. This study, therefore, recommends the need for cross-sector collaboration to maximize the role of social media in enhancing culinary promotion and strengthening Lombok’s tourism image.